Size spectra and source apportionment of fine particulates in tropical urban environment during southwest monsoon season. (January 2019) - Zong, Yichen; Botero, Maria L.; Yu, Liya E.; Kraft, Markus
Abstract: In this study, we carried out high time-resolution measurements of particle number concentration and size distribution (5–1000 nm) in Singapore, which represents a tropical urban environment. The measurements were taken during the southwest monsoon season in 2017 using a fast-response differential mobility spectrometer at a sampling rate of 1 Hz. In the measurement, short-lived nucleation events were found prominent at early afternoon because of the abundant incoming radiation that enhances the photochemical reactions in atmosphere. For the first time in the region, a five-factor positive matrix factorization approach was applied to the size spectra data. Based on particle number concentration, two sources within nucleation mode ( < 30 nm) were resolved and account for 43% of total number concentration, which is higher than the available monitoring data in other big cities. Among the sources, O3 -related atmospheric photochemical reactions with peak size at 10–12 nm is a unique factor and prominent in early afternoon nucleation events. The findings of this work can serve as a baseline for assessing influence of local and cross-border airborne emissions during various seasons in the future. Graphical abstract: Image 1 Highlights: Size spectra of airborne fine particulates were measurement at 1 Hz frequency. Significant nucleation events were observed during southwest monsoon season. Source apportionment on particle size spectra data was performed in Singapore. A unique nucleation source was found that correlates with O3 -related reactions. Abstract : Short-lived nucleation is found prominent in tropical urban environment. A unique source is discovered correlated with O3 .